Review : Studi Aktivitas Antioksidan dari beberapa Jenis Perlakuan Kopi - Habibur Umami Amrullah; Sandi (Program Studi Akuntansi IKOPIN, 2022)
Coffee, being one of the most popular beverages in the world, is a rich source of antioxidants. This review aims to determine the antioxidant activity content of several coffee treatments. We reviewed from several journals about the antioxidants of coffee made. Of all the treatments where the fermentation process can increase the antioxidant activity of green coffee beans. The greatest antioxidant activity was found in the study of Kwak et al. (2018) using S. cerevisiae with an increase of 23.33 M TE/mL in the ORAC method and 53.13% in the SOD method. This is supported by fermentation factors such as the amount of yeast used as a starter.